Perceptions of students in colleges belonging to the science and technology cluster of the University of the Philippines Diliman on Library and Information Science - Santos, Jonathan F. (School of Library and Information Studies, University of the Philippines Diliman, 2007)
This study was undertaken to determine how non-Library and Information Science (LIS) students of the University of the Philippines Diliman, particularly students belonging to the Science and Technology Cluster courses, perceive the field of LIS and the factors that affect their perceptions.